Midostaurin and cyclosporine drug interaction: A case report. (29th November 2019) - Mancini, Robert; LaMontagne, Leslie; Williams, Travis; Kreisle, William; Petersen, Finn
Abstract: What is Known and Objective: Allogeneic stem cell transplantation patients are often on immunosuppression including calcineurin inhibitors post‐transplant for prevention of graft‐versus‐host disease. Recent data suggested that addition of midostaurin, a FLT‐3 mutant kinase inhibitor, maintenance can reduce risk of relapse by 46% at 18 months post‐transplant. Case Description: Patient is a post‐allogenetic stem cell transplant patient started on midostaurin for maintenance therapy. Patient had stable serum levels of cyclosporine with a sudden 70% increase in serum level shortly after starting midostaurin. Patient had no other medication changes or laboratory abnormalities that would suggest the change was caused by alternate factors. What is New and Conclusion: This data suggest that midostaurin and cyclosporine have a possible previously unidentified drug interaction leading to elevation immunosuppression serum levels that need to be accounted for in practice. Abstract : This is a case report of a patient receiving post‐allogeneic stem cell transplant midostaurin for FLT3+ acute myeloid leukemia. Upon initiation of this medication, with no other changes, the patient's cyclosporine level increased dramatically. This report suggests more information is needed to elucidate the likelihood of this interaction and appropriate adjustment/monitoring of concomitant immunosuppression in patients with maintenance midostaurin.